Pemanfaatan dan Strategi Pemasaran Rotan Irit (Calamus Trachycoleus) di Kecamatan Montallat Kabupaten Barito Utara - Nursiah Nursiah; Jumri Jumri; Mohammad Noor Gustaf Rizal (Universitas Batanghari Jambi, 2023)
This study aims to describe the form of efficient use and analyze the marketing strategy of economical rattan. This research was conducted in the village of Tumpung Laung I and the village of Montallat II, North Barito Regency. Sampling using purposive sampling and saturated sampling (census). Data collection techniques by observation, interviews and questionnaires. Analysis of the data used is using SWOT and descriptive qualitative. Based on the results of the research, the people of Tumpung Laung I and Montallat II used the economical rattan type . The community makes economical rattan as income by harvesting and collecting rattan which is sold to collectors in the form of raw rattan and the community also uses economical rattan as a raw material for making rattan crafts. The economical rattan marketing strategy in Tumpung Laung I lies in quadrant III or in a strategic position to minimize weaknesses to take advantage of opportunities or in the WO strategy. The suitable marketing strategy in Tumpung Laung I is a turn-around strategy, while the economical rattan marketing strategy in Montallat II is located in quadrant I or in a very profitable strategic position, namely because it has opportunities and strengths so that it can take advantage of existing opportunities or on SO strategy, from the analysis of the suitable marketing strategy in Montallat II is an aggressive strategy.